2002
DOI: 10.1101/lm.48502
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinase Activity in the Entorhinal Cortex Is Necessary for Long-Term Spatial Memory

Abstract: Lesion studies have provided evidence that the entorhinal cortex (EC) participates in spatial memory. However, the molecular cascades that underlie memory-associated changes in the EC and its specific role in spatial memory, however, have not been clearly delineated. Recently, it has been shown that activation of extracellular signal-regulated kinase (Erk, a mitogen-activated protein kinase family member) in the dorsal hippocampus is necessary for spatial memory. To examine whether similar mechanisms are used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 61 publications
4
39
0
2
Order By: Relevance
“…In previous reports, long-term memory storage has been correlated to the activation of Erk within specific brain structures (Berman et al, 1998;Blum et al, 1999;Schafe et al, 2000;Hebert and Dash, 2002). This is consistent with our results indicating a requirement for Erk activation in the hippocampus for long-term memory of trace fear conditioning.…”
Section: Trace Cs-us Associative Memorysupporting
confidence: 82%
See 1 more Smart Citation
“…In previous reports, long-term memory storage has been correlated to the activation of Erk within specific brain structures (Berman et al, 1998;Blum et al, 1999;Schafe et al, 2000;Hebert and Dash, 2002). This is consistent with our results indicating a requirement for Erk activation in the hippocampus for long-term memory of trace fear conditioning.…”
Section: Trace Cs-us Associative Memorysupporting
confidence: 82%
“…In mammals the activation and necessity of Erk within structures including the insular cortex (Berman et al, 1998), the hippocampus (Blum et al, 1999), the entorhinal cortex (Hebert and Dash, 2002), and the amygdala (Schafe et al, 2000) have been demonstrated to be required in various memory tasks. Unlike lesion studies, inhibition of Erk allows for the assessment of long-term memory storage within a structure without causing a generalized dysfunction evidenced by intact acquisition (Blum et al, 1999) and short-term memory (Martin et al, 1997;Schafe et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…ERK has been implicated in both synaptic plasticity (English and Sweatt 1996;Martin et al 1997) and the consolidation of numerous learning paradigms (Atkins et al 1998;Berman et al 1998;Blum et al 1999;Hebert and Dash 2002;Kelly et al 2003). More recently, studies have established that activation of ERK is not only necessary for memory consolidation, but reconsolidation as well.…”
Section: Protein Kinasesmentioning
confidence: 99%
“…It has been suggested that the dopamine D1 receptor extracellular signal-regulated kinase (ERK1/2) signaling pathway in the PFC is critically involved in molecular adaptations that are necessary for long-term behavioral and neuronal plasticity (Nagai et al 2007). The phosphorylation of ERK has been shown to be a correlate for plasticity (for review, see Sweatt 2004) and long-term memory for taste (Berman et al 1998), fear conditioning , and spatial tasks (Blum et al 1999;Hebert and Dash 2002). Nagai et al (2007) have found that dopamine D1 receptors regulate protein synthesis-dependent long-term recognition memory via ERK in the PFC.…”
mentioning
confidence: 99%